1998
DOI: 10.1161/01.cir.98.11.1116
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Animal and Clinical Experiences Using an Electromechanical Endocardial Mapping Procedure to Distinguish Infarcted From Healthy Myocardium

Abstract: Background-A catheter-based left ventricular (LV) endocardial mapping procedure using electromagnetic field energy for positioning of the catheter tip was designed to acquire simultaneous measurements of endocardial voltage potentials and myocardial contractility. We investigated such a mapping system to distinguish between infarcted and normal myocardium in an animal infarction model and in patients with coronary artery disease. Methods and Results-Measurements of LV endocardial unipolar (UP) and bipolar (BP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
2
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 22 publications
9
124
2
3
Order By: Relevance
“…12,29 Moreover, the identical LV anatomic site that was observed to be improved by EMM was consistently observed to be improved by SPECT Tc 99m sestamibi myocardial perfusion imaging as well. Initial experience with catheterbased GTx in the single-blind study referred to above confirmed these findings by demonstrating reproducibility of the SPECT and EMM maps from baseline to post-mock procedure, followed by site-specific improvement in both SPECT and EMM 90 days after the patient crossed over to VEGF2 GTx.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…12,29 Moreover, the identical LV anatomic site that was observed to be improved by EMM was consistently observed to be improved by SPECT Tc 99m sestamibi myocardial perfusion imaging as well. Initial experience with catheterbased GTx in the single-blind study referred to above confirmed these findings by demonstrating reproducibility of the SPECT and EMM maps from baseline to post-mock procedure, followed by site-specific improvement in both SPECT and EMM 90 days after the patient crossed over to VEGF2 GTx.…”
Section: Discussionmentioning
confidence: 70%
“…In each of these studies, interpretation of symptomatic outcome in particular was complicated by the lack of a placebo-treated control group. Inclusion of a control group was recently facilitated by the advent of catheter-based GTx, which minimized the ethical dilemma of blinded placebo controls, 7,8,12 whereas a previous 6-patient pilot trial using this approach showed reduction in anginal symptoms and nitroglycerin use in VEGF2 versus placebo patients. This trial was limited because it was a single-blind design in which patients randomized to the control arm underwent a mock procedure (the catheter was advanced to the LV, but no injection was performed).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 -21 It can be postulated that LELI can be delivered to the myocardium in humans via fiber optics in the catheter of the nonfluoroscopic in vivo navigation and mapping technology 19 currently in use in experimental animals and in humans. 20,21 The LELI energy can also be applied during or after the procedure of balloon angiography by use of a catheter with a central canal bearing a fiber optic, through which the laser energy can be delivered transversely (360°) to the infarcted area. Furthermore, as an adjunct procedure to other, increasingly popular approaches for repairing ischemic myocardium (angioplasty, stenting, grafting, transmyocardial revascularization, etc), the cardioprotective effect of LELI may likewise be beneficial at minimal or no additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…A comparação desta via com a cirúrgica foi posteriormente realizada, em um grupo pequeno de pacientes, revelando resultados similares em relação à eficácia 23 . Outra opção de acesso foi demonstrada com a utilização do sistema de mapeamento eletromecânico tridimensional, o qual fornece a vantagem de permitir a diferenciação entre tecido miocárdico viável e cicatricial, facilitando a injeção precisa no segmentoalvo 24,25 . Neste estudo, foram realizadas injeções transendocárdicas com uso de cateter Myostar (sistema NOGA -Biosense Webster) e acesso vascular percutâneo em cinco pacientes com IAM anterior prévio 20 .…”
Section: Mioblastosunclassified